REVIEW OF INDONESIA'S EMPLOYMENT ARRANGEMENTS IN FACING ASEAN ECONOMIC COMMUNITY - Ayu Permatasari; Chatrina Febriani Pratiwi; Medika Era Wijaya (Faculty of Law Universitas Lampung, 2021)
The AEC is the founder of the ASEAN Community and the formation of regional economic integration, which was implemented in 2015. The implementation of ASEAN is made up of the flow of services/goods on a single product and market basis, skilled labour, investment, and free capital flows between countries in the ASEAN region. As an opportunity at the time of employment and as a substitute for unemployment, the Indonesian state must be utilized free of skilled labour. The issues that have arisen are how the employment arrangements in Indonesia are? How to optimize Indonesia’s employment arrangements in the AEC era? The method of approaching this research is the normative juridical method. The research shows that there are arrangements in the field of manpower that help realize quality human resources and skilled labour. It also states that Law No. 13 of 2003 on Manpower and other policies that provide job training and certification of work competencies that optimize employment to be more qualified, skilled, and competitive and recognized by other ASEAN countries in facing the AEC.